Kangaroo Care for Hospitalized Infants with Congenital Heart Disease. Issue 3 (May 2020) - Lisanti, Amy Jo; Buoni, Alessandra; Steigerwalt, Megan; Daly, Michelle; McNelis, Stephanie; Spatz, Diane L.
Abstract: Background: Kangaroo care (KC), or skin-to-skin care, occurs when an infant is dressed in a diaper and held to a parent's bare chest. This form of holding has been shown to have many benefits for hospitalized infants and has been shown to be a safe and feasible intervention to support infants with congenital heart disease. Despite known benefits, KC was not implemented routinely and consistently in our cardiac center for infants with congenital heart disease. The purpose of this project was to support use of KC as a nursing intervention for hospitalized infants with congenital heart disease and their parents. Methods: A KC quality improvement committee formed to develop strategies to increase frequency of KC, including the creation of a new nursing policy and procedure on KC for infants, adaptation of the electronic health record to facilitate KC documentation, education, and supporting translation of KC into practice through the cardiac center's first Kangaroo-A-Thon. Results: Twenty-six nurses initiated KC 43 times with 14 patients over the 8-week period for the Kangaroo-A-Thon. No adverse events were reported as a result of infants being held by their parents in KC. Conclusion: Our local initiative provided preliminary evidence that KC can be safely integrated into standard care for hospitalized infants with congenital heart disease. Formal standards and procedures, along with creative initiatives such as a Kangaroo-A-Thon, can be a first step toward fostering the translation of KC into practice. Abstract : Skin-to-skin care, also known as kangaroo care, has many known benefits for newborns. In this quality improvement project, nurses caring for infants with congenital heart disease requiring corrective surgery in the first few weeks of life developed processes to apply kangaroo care to this patient population and evaluated outcomes. Kangaroo care appears to be feasible and safe for infants with congenital heart disease before and after surgery.